2016
DOI: 10.4317/medoral.21111
|View full text |Cite
|
Sign up to set email alerts
|

Longterm quality of life after oncologic surgery and microvascular free flap reconstruction in patients with oral squamous cell carcinoma

Abstract: BackgroundQuality of life (QoL) has become increasingly important in cancer treatment. It refers to the patient’s perception of the effects of the disease and therapy, and their impact on daily functioning and general feeling of well being.Material and Methodsn this prospective study, a total of 100 patients treated at our institution, completed the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 questionnaire and the specific EORTC QLQ-H&N35 module. The questionnaires were distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In 2016, Peisker and colleagues ( 25 ) conducted a long-term study on the quality of life of patients with oral squamous cell carcinoma undergoing cancer surgery with the vascularized reconstruction of a free flap. They concluded that the surgery was successful, but the patient’s quality of life was diminished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Peisker and colleagues ( 25 ) conducted a long-term study on the quality of life of patients with oral squamous cell carcinoma undergoing cancer surgery with the vascularized reconstruction of a free flap. They concluded that the surgery was successful, but the patient’s quality of life was diminished.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life and its measurement values are becoming more important every day in oncological therapies. Therefore, several recent studies have been published in the scientific literature ( 25 ). The specific system to objectively quantify the quality of life of patients has been and remains difficult, yet there are several valid and useful methods in the field of oncology.…”
Section: Discussionmentioning
confidence: 99%
“…This type of analysis has been performed comparing locoregional rotational flaps and FFs, but not STSGs. 18,24,[27][28][29][30][31][32] We acknowledge the limitations of this study. The low questionnaire response rate and low number of study subjects limited statistical comparisons and meaningful multivariate analyses.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In recent decades, the cornerstone of the assessment of cancer treatment efficacy was the survival rate, as well as the recurrence or complication rates. Nowadays, the focus is also on the impact of the disease on patients' quality of life (QoL) [5]. The consequences of the malignancy on patients' psychosocial behavior can be assessed during three phases: at diagnosis, during treatment, and during long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%